2016
DOI: 10.1002/nur.21741
|View full text |Cite
|
Sign up to set email alerts
|

Severe Maternal Morbidity and Postpartum Depressive Symptomatology: A Prospective Double Cohort Comparison Study

Abstract: The adverse consequences to mothers of postpartum depression are well-documented, and risk factors are of interest. There is limited evidence on postpartum depression among women with severe maternal morbidity, defined as potentially life-threatening conditions during pregnancy, childbirth, or soon after termination of pregnancy. We compared postpartum depressive symptoms of postpartum women aged 18 and older who delivered in two tertiary referral hospitals in 2014 in Kelantan, Malaysia, and had (n = 145) or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
(62 reference statements)
1
9
0
2
Order By: Relevance
“…We found that severe maternal complications have a little effect on mental health and quality of life in our population irrespective whether they lost their baby or not. This finding is in line with previous studies done in Malaysia [10] and England [5] which equally did not find significant differences when screening for depression between women with and without severe maternal complications. However, there are other studies that found a statistically significant difference between the two groups [7,9], while another study [8] found that the association between depression and severe maternal morbidity was present only for women who lost their baby.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that severe maternal complications have a little effect on mental health and quality of life in our population irrespective whether they lost their baby or not. This finding is in line with previous studies done in Malaysia [10] and England [5] which equally did not find significant differences when screening for depression between women with and without severe maternal complications. However, there are other studies that found a statistically significant difference between the two groups [7,9], while another study [8] found that the association between depression and severe maternal morbidity was present only for women who lost their baby.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, most studies (e.g., conducted in Morocco [7], Benin [8], and Burkina Faso [9]) found that women with MNM had an increased risk of developing depression in the post-partum year, especially if they had lost their baby. On the contrary, similar studies in Malaysia [10] and England [5] found no significant difference regarding the risk of depression among women with and without MNM. Similarly, there is contradicting evidence regarding the association between hospital admission due to pregnancy complications and post-traumatic stress disorder (PTSD) [5,6,11].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In Asia, pregnancy complications, negative childbirth experiences, and severe morbidity at the time of childbirth have been associated with subsequent postpartum depressive symptomatology (Gausia et al, 2012; Giri et al, 2015; Lyengar, Yadav, & Sen, 2012; Shivalli & Gururaj, 2015). Some studies, however, have not found a significant relation between severe medical complications during or immediately after pregnancy with postpartum depressive symptoms, perhaps because the occurrence of severe morbidity is quite rare (Norhayati, Nik Hazlina, Aniza, & Asrenee, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Na Argentina, Mathisen et al 20 constataram 37,2% dessa associação entre as mulheres puérperas. Outro dado importante sobre essa associação observado por Norhayati et al 10 foi a presença de fatores de risco relacionados a problemas de saúde, complicações obstétricas e baixo apoio social 21 .…”
Section: ▄ Métodounclassified